Researching and academic writing using citation management tool (CMT) / Laili Ashikeen Awang Puteh … [et. al.] - Awang Puteh, Laili Ashikeen; Mat Yatin, Saiful Farik; Zamberi, Farleen Azrina; Bahari, Farhana (Universiti Teknologi MARA Cawangan Selangor, 2019)
The focus of this paper is on the appropriate criteria in evaluating and choosing the right citation management tools (CMT). As the number of citation management tools increased in recent years, users have problems in choosing the best and right citation management tools that would suit their needs. There are approximately thirty citation management tools worldwide, and users need to take into consideration several aspects which will eventually help them in deciding the citation management tool that suitable to their unique requirement and situation. There are also some users who are not familiar with the choices of the tools and having problems in using them. This kind of users tends to shift to the less complicated way which is manually creating the citation. This paper discussed further on the issues in using the citation management tools and also outlined seven important criteria to be considered in deciding the right citation management tools.